Research ‘side-spaces’ and the criticality of Auckland, New Zealand, as a site for developing a queer Pacific scholarly agenda - Thomsen, Patrick (New Zealand Sociology, 2026)
Social science research focused on the specific needs of Pacific Rainbow+ communities is relatively scant both in New Zealand and abroad. In this article, I explore the generative possibilities of Auckland, New Zealand, as site for the intentional development and growth of a queer Pacific scholarly agenda. I argue that Auckland in general, and its university in particular, are sites of ongoing Māori resistance to settler-colonialism, provides research ‘side-spaces’ that create opportunities for a queer Pacific scholarly agenda. I show why it is currently not safe for queer Pacific scholars based in Pacific countries to practise the type of queer Pacific research agenda I call for in Auckland. I also highlight the inherent contradictions, tensions and possibilities for queer Pacific research in Auckland, New Zealand. New Zealand-based Pacific queer scholars are urged to occupy these research side-spaces before they, too, become Pākehā and colonial sites of knowledge production.